Fungal Nanotechnology - Abd-Elsalam, Kamel A. (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Fungal Nanotechnologies (FN) 1 and 2 provide updated and comprehensive information that deals with the green and sustainable production of metal- and organic-based nanostructures by various fungal species. Additionally, intracellular and extracellular mechanisms will be investigated, as well as fungal nanotechnology applications in the biomedical, environmental, and agri-food sectors. FN is still in its infant stage; therefore, many studies should be focused on this area. Plants, animal and humans will benefit greatly from this, and efficient and ecologically friendly approaches should be created.